2007
DOI: 10.1515/jpem.2007.20.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemic Rickets in Opsismodysplasia

Abstract: We now demonstrate an association between opsismodysplasia, hypophosphatemic rickets, and FGF23 elevation. Screening phosphorus levels may thus uncover a potentially treatable component of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…35 Opsismodysplasia, a rare hereditary spondylo(epi) chondrodysplasia, is also characterized by hypophosphatemia, abnormal vitamin D metabolism and elevated FGF-23 levels, but the disease-causing gene mutation has not been identified. 36 Elevated FGF-23 levels also cause acquired hypophosphatemic disorders, such as tumor-induced osteomalacia, and are an important adaptive response in CKD. 37 …”
Section: Mutations That Elevate Fgf-23 Levelsmentioning
confidence: 99%
“…35 Opsismodysplasia, a rare hereditary spondylo(epi) chondrodysplasia, is also characterized by hypophosphatemia, abnormal vitamin D metabolism and elevated FGF-23 levels, but the disease-causing gene mutation has not been identified. 36 Elevated FGF-23 levels also cause acquired hypophosphatemic disorders, such as tumor-induced osteomalacia, and are an important adaptive response in CKD. 37 …”
Section: Mutations That Elevate Fgf-23 Levelsmentioning
confidence: 99%
“…2,3 The outcome is variable with lethality due to respiratory complications in many of them. 5,6,7 It is interesting to note severe polyhydramnios in the antenatal period, usually a feature of severe chondrodysplasias, was also seen here and required amnioreduction. Intelligence is usually normal.…”
Section: Discussionmentioning
confidence: 56%
“…So it was suggested that temporary hypophosphatemia occur possibly by pilates exercise. Prolonged hypophosphatemia can cause rickets [38], and it finally occurs osteomalacia even in normal serum Ca condition [39]. In addition, according to the report from Mehrotra et al .…”
Section: Discussionmentioning
confidence: 99%